IrAM-An alpha2-macroglobulin from the hard tick Ixodes ricinus: characterization and function in phagocytosis of a potential pathogen Chryseobacterium indologenes - Buresova, Veronika; Hajdusek, Ondrej; Franta, Zdenek; Sojka, Daniel; Kopacek, Petr (Developmental and comparative immunology, 2009)
The universal protease inhibitors of the alpha(2)-macroglobulin (alpha(2)M) family are evolutionarily conserved constituents of innate immunity, presumably because they guard organisms against undesired proteolytic attacks of a different origin. Here, we determined the primary structure of alpha(2)-macroglobulin from the hard tick Ixodes ricinus (IrAM) by sequencing of overlapping PCR products. Predicted disulfide and glycosylation patterns, post-translational cleavage and alternative splicing within its 'bait region' demonstrate that IrAM is closely related to the alpha(2)-macroglobulin from the soft tick Ornithodoros moubata. The IrAM message is expressed in all tick developmental stages and tissues, except for the gut, and the protein was detected to be mainly present in the hemolymph. Silencing of IrAM by dsRNA interference markedly reduced the phagocytosis of a potential pathogen, Chryseobacterium indologenes, by tick hemocytes both in vitro and in vivo. In contrast, phagocytosis of the Lyme disease spirochete Borrelia burgdorferi or a commensal bacteria Staphylococcus xylosus was not affected by the IrAM knock-down. Similar results were obtained upon deactivation of all thioester proteins in tick hemolymph by methylamine. We have further demonstrated that phagocytosis of C. indologenes is dependent on an active metalloprotease secreted by the bacteria. These data indicate that interaction of tick alpha(2)-macroglobulin with a protease of an invading pathogen is linked with cellular immune response.
Keywords: metaloproteasy; RNA interference; sekvence nukleotidů; klíště; fenantroliny; fagocytóza; hemolymfa; alfa-makroglobuliny; Hemocytes; molekulární sekvence - údaje; Amino Acid Sequence; alpha-Macroglobulins; sekvenční seřazení; Phenanthrolines; Metalloproteases; Animals; Chryseobacterium; hemocyty; methylaminy; zvířata; sekvence aminokyselin; Ixodes; Phagocytosis; Methylamines; Molecular Sequence Data; Base Sequence; Hemolymph; RNA Interference; Sequence Alignment